Pengaruh Verbal Bullying Terhadap Kepercayaan Diri Siswa Sekolah Dasar - Nanik Ismiati; Putri, Dya Ayu Agustina; Sari, Eka Yuliana; Bariroh, Ummi; Fitriana, Iin Mahlia (Alpatih Harapan Semesta, 2025)
Bullying behavior at school can create conditions that hinder students' development, both in academic and social aspects. Bullying can have a negative impact resulting in feelings of discomfort for students. This research aims to determine the effect of verbal bullying on students' levels of self-confidence, by comparing students who experienced verbal bullying and those who did not. The instrument used in this research was a self-confidence instrument in the form of a statement questionnaire. An instrument is said to be reliable if the observed score has a high correlation with the actual score. It is further stated that reliability is the correlation coefficient between two observed scores obtained from the measurement results process using parallel tests. Based on the results of research conducted regarding the influence of verbal bullying on students' self-confidence, it can be concluded that there is a significant influence of verbal bullying on students' self-confidence. Students who experience verbal bullying tend to have low self-confidence, compared to students who do not experience verbal bullying